Fall, Creation, and Redemption in Neil LaBute's The Shape of Things - Olson, Duane (The journal of religion and film, 2004)
The Shape of Things is a contemporary restatement of the biblical story of the fall. Unlike other recent films about a fall from innocence, like Pleasantville and The Truman Show, which portray the fall as a rise into a meaningful life with limited and guarded harshness, LaBute's drama presents the fall as entrance into a world of unreserved individual and social depravity. I analyze LaBute's creative interplay with the biblical story and show the different directions of sinfulness that the film exposes, including the social critique underlying those directions. While the film presents no social redemption, I disclose the brief glimmers of the possibility of individual redemption that shine through it.